Investigation of cytotoxic properties of some isoindole-related compounds bearing silyl and azide groups with in vitro and in silico studies - Tan, Ayse; Kose, Aytekin; Mete, Derya; Sanli-Mohamed, Guelsah; Kishali, Nurhan H.; Kara, Yunus (Taylor & Francis Ltd, 2023)
This study aims to evaluate the synthesis of isoindole-1,3-dione analogues and their cytotoxic potential. A549 and HeLa cells exposed to 250-100-50-25 mu M doses of each derivative were incubated for 24, 48, and 72 h. The cytotoxicity of the isoindole-1,3-dione derivatives was analyzed using the cell growth inhibition assay and the cell membrane damage test. (3aR,5R,6R,7aS)-5-Azido-2-benzyl-6-hydroxyhexahydro-1H-isoindole-1,3(2H)-dione (1d), (3aR,5R,6R,7aS)-5-azido-6-((tert-butyldiphenylsilyl)oxy)-2-ethylhexahydro-1H-isoindole-1,3(2H)-dione (2a), and (3aR,5R,6R,7aS)-5-azido-6-((tert-butyldiphenylsilyl)oxy)-2-methylhexahydro-1H-isoindole-1,3(2H)-dione (2b) compounds inhibited the growth of the A549 and HeLa cells caused membrane damage and exhibited a dose-dependent cytotoxic effect on lung and cervical carcinoma cells. The effect of tert-butyldiphenylsilyl (TBDPS) groups on cytotoxicity was observed in compounds 2a and 2b, but not in the other compounds. Considering the effect of groups attached to the nitrogen atom, the best activity was exhibited in 2b molecule to which the methyl group is attached. Additionally, the interactions of compounds (3aR,5R,6R,7aS)-5-azido-6-hydroxy-2-methylhexahydro-1H-isoindole-1,3(2H)-dione (1b), 1d, 2a and 2b with mammalian rapamycin target, human ribosomal S6 kinase 1 and human epidermal growth factor receptor were investigated by molecular docking studies, . According to the docking results, 2a and 2b compounds containing a TBDPS group have stronger binding energies than 1b and 1d compounds against all target receptors.
Keywords: Isoindole-1,3-Dione; Cytotoxity; Molecular Docking; A549 And Hela Cell Lines; Silyl Ether; Norcantharidin Analogs; Nitrogen-Heterocycles; Anticancer Activity; Derivatives; Kinase; Cantharimide; Growth